Plant Molecular Evolution 2000
DOI: 10.1007/978-94-011-4221-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Myrosinase: gene family evolution and herbivore defense in Brassicaceae

Abstract: Glucosinolates are a category of secondary products present primarily in species of the order Capparales. When tissue is damaged, for example by herbivory, glucosinolates are degraded in a reaction catalyzed by thioglucosidases, denoted myrosinases, also present in these species. Thereby, toxic compounds such as nitriles, isothiocyanates, epithionitriles and thiocyanates are released. The glucosinolate-myrosinase system is generally believed to be part of the plant's defense against insects, and possibly also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
358
2
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(376 citation statements)
references
References 125 publications
4
358
2
8
Order By: Relevance
“…The differential expression of CYP83A1 in these ecotypes partially explains the different basal glucosinolate profiles in the Col and Ler ecotypes (Kliebenstein et al, 2001a) and the higher overall glucosinolate content of the Ler ecotype (Jander et al, 2001). Presumably these different basal levels of glucosinolates contribute to variations in ecotype resistance to insect predators as myrosinases release toxic glucosinolate derivatives (Rask et al, 2000). But, in the long run, it is the induced levels of glucosinolates that provide the most effective, sustained protection against insect damage.…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of CYP83A1 in these ecotypes partially explains the different basal glucosinolate profiles in the Col and Ler ecotypes (Kliebenstein et al, 2001a) and the higher overall glucosinolate content of the Ler ecotype (Jander et al, 2001). Presumably these different basal levels of glucosinolates contribute to variations in ecotype resistance to insect predators as myrosinases release toxic glucosinolate derivatives (Rask et al, 2000). But, in the long run, it is the induced levels of glucosinolates that provide the most effective, sustained protection against insect damage.…”
Section: Discussionmentioning
confidence: 99%
“…In Brassica vegetables, there are typically 0.5-28 µmol aliphatic/ aromatic glucosinolates per gram dry weight and 0.7-8 µmol indolyl glucosinolates per gram dry weight. Glucosinolates are normally localized to the cytoplasm of plant tissue [9] . Myrosinase is expressed on the external surface of the plant cell wall, so it cannot access the glucosinolates [9] .…”
Section: Biosynthesis and Metabolismmentioning
confidence: 99%
“…Plants in the Brassicaceae family, which includes Arabidopsis thaliana, accumulate glucosinolates, a family of secondary metabolites that are sources of thioacyanates and other breakdown products that are toxic to some aphids (Rask et al, 2000;Halkier and Gershenzon, 2006). Levy et al, (2005) showed that the expression level of the IQD1 (At3g09710) gene, which encodes a transcription factor that is responsible for glucosinolate accumulation, impacts host plant choice by GPA.…”
Section: Glucosinolates-a Brassicaceae-specific Chemical Defensementioning
confidence: 99%
“…However, when acted upon by myrosinases, glucosinolates produce toxic thiocyanates and other breakdown products that act as defensive compounds against insects (Chew, 1988;Louda and Mole 1991;Rask et al, 2000). In Arabidopsis, β-thioglucoside glucohydrolases encoded by TGG1 and TGG2 (At5g25980 and At5g26000) contribute to the majority of the myrosinase activity (Barth and Jander, 2006).…”
Section: Glucosinolates-a Brassicaceae-specific Chemical Defensementioning
confidence: 99%